Fat destabilization and melt-down of ice creams with increased protein content. (April 2015) - Daw, E.; Hartel, R.W.
Abstract: Effects of individual protein sources or blends on microstructure and melt-down rates of ice cream were investigated. Ice creams were formulated with non-fat dry milk (NFDM), milk protein concentrate, whey protein isolate (WPI), or procream to total protein concentrations of 4–10%. Ice creams were also made with protein blends containing 4% protein from NFDM with additional WPI or procream to total protein concentrations of 6–10%. Mean ice crystal and air cell sizes and overrun were not significantly impacted by protein source, blend, or concentration. Partially-coalesced fat decreased with increasing protein content, except in ice creams made with only NFDM. Melt rate tended to increase with protein content, with the exception of ice creams made with procream, which gave rapid melt rates at all protein concentrations. Protein type, blend and concentration were hypothesized to affect the properties of the emulsion interface, leading to differences in partial coalescence and melt-down rates.